Structural and physiological effects of chromium uptake in the seagrass Halophila stipulacea. (March 2021) - Malea, Paraskevi; Mylona, Zoi; Panteris, Emmanuel; Kevrekidis, Theodoros
Highlights: Halophila stipulacea can act as a bioindicator of ambient Cr (VI) bioavailability. Cr can be toxic to seagrasses at environmentally relevant Cr (VI) concentrations. Actin filaments and endoplasmic reticulum are sensitive markers of Cr (VI) Regression models describe the relationship effect onset vs. Cr (VI) exposure. Uptake rate rather than tissue concentration relates to the onset of toxic effects. Abstract: This work aims to provide insight on the effects of chromium (Cr) uptake in seagrasses at environmentally relevant exposure concentrations; information on this issue can further increase the utility of marine angiosperms as indicators of trace metal contamination. Cr uptake kinetics, effects on physiological and structural cell traits, and the uptake-effects relationship in Halophila stipulacea leaves incubated in 0.01–10 mg L −1 (0.2–200 μM) of Cr (VI) were examined. An initial uptake was followed by a decrease at 0.01–0.5 mg L −1 (0.2–10 μM); at higher exposures, the fit of uptake data to a Michaelis-Menten-type equation was significant (p < 0.001). The mean tissue concentration over the exposure period, and the highest tissue concentration attained both increased as exposure concentration (Cw ) increased from 0.05 to 10 mg L −1 (1 to 200 μM); uptake rate generally increased with Cw . Cytotoxic effects occurred even at 0.01 mg L −1 (0.2 μM). Actin filaments (AFs) and endoplasmic reticulum (ER) were impacted in a dose- and time- dependent pattern, while microtubule integrity was not markedly affected even at the highest exposure. AF disruption in differentiating cells initiated at 0.01 mg L −1 (0.2 μM), while ER disorganization did so at 0.1 mg L −1 (2 μM); regression equations described the relationships of Cw vs. time required for effect onset, and of Cw vs. AF disturbance progress. Elevated levels of hydrogen peroxide (H2 O2 ) were detected on the 2d. In addition, a significant reduction in epidermal cell viability appeared at 5–10 or 10 mg L −1 (100–200 or 200 μM), depending on the leaf age. The lowest tissue concentration associated with effect onset was 31.05 μg g −1 dry wt (2d, 5 mg L −1 ); at lower exposures, higher tissue concentrations did not coincide with impact, implying that the uptake rate rather than the tissue concentration relates to the effect onset. The above suggest that (a) Cr (VI) may pose a high risk to seagrass meadows, (b) H. stipulacea can act as a bioindicator of ambient Cr (VI) bioavailability, mainly at elevated exposure concentrations, (c) AF and ER disturbances in seagrass leaf cells could be considered as sensitive biomarkers of Cr (VI)-induced stress, (d) regression equations describing the relationships Cw vs. time required for effect onset and Cw vs. effect progress increase the utility of AF and ER impairment as biomarkers, and (e) the time frame of the exposure should be considered in the interpretation of tissue residues. Our findings improve the utility of seagrasses as indicators of trace metal contamination and could be utilized in the overall effort for seagrass meadows conservation.